Pendidikan Karakter Berbasis Sistem Islamic Boarding School Multidisipliner Dalam Mempertahankan Kebudayaan Dan Moderasi Beragama - Yanto, Masti; Abidin, Zeinal; Maizah, St.; Inayati, Mahfida (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Character education based on the multidisciplinary Islamic boarding school system has an important role in maintaining national culture and identity. Character education is an effort to form strong individuals, good morals, and awareness of human values. The Islamic boarding school system, with an educational environment centered on Islamic values, provides an ideal framework for developing student character. In this context, multidisciplinary character education emphasizes the integration of various scientific disciplines, including religion, science, arts and humanities. This helps students understand that moral and cultural values can be integrated into all aspects of their lives. Character education also encourages students to become responsible leaders in society.